Behavioural and physiological ecology of the Namib Desert dune ant, Camponotus detritus emery - Curtis, Barbara (Department of Biological Sciences, 2023)
The ecology of Camponotus detritus was examined over two years at six sites across the Namib Desert. This common species was found to fill an important role in the dune ecosystem as the major honeydew consumer, apparently limited chiefly by intraspecific competition for food. Each colony, comprising one to four nests with a mean of 3 404 workers per nest, maintained a discrete foraging territory. Nests were constructed in sand beneath perennial vegetation. Nest density was 0,3 - 0,9 ha-1 . Worker abundance was lowest near the coast, highest in the central dunes and intermediate inland toward the east. The abundance of honeydew producing scale insects showed a similar pattern. There was no marked seasonality in the intensity of foraging activity or in brood production, suggesting a constant food supply which is in turn maintained by the regular occurrence of advective fog. Both light and temperature affected surface activity, which was bimodal in summer and unimodal in winter, ceasing when surface temperature exceeded about 55 ° C. Due to a steep thermal gradient above the sand during midday in summer the air temperature experienced by ants at 5 mm was 10 - 15 ° C lower than surface temperature. Although primarily diurnal, some workers remained at their foraging grounds overnight. Laboratory studies showed that the mean preferred temperature of workers and brood was 35 ° C at 100 % rh and 31 - 33 ° C at 30 % rh. The CTmax of workers was 53 ° C at 100 % and 30 % rh and CT . was 4,57 ° C at 100 % rh. min Workers tolerated -1 ° C, 95 % rh; 45 ° C, 95 %rh and 45 ° C, 45 % rh for 24 hours. Water loss increased with increasing saturation deficit at 35 ° C but was lower at 25 ° C and 24 rrrn Hg than at 35 ° C and 21 mm Hg. Large workers had lower rates of water less and survived longer than smaller workers. Groups last significantly less water at 25 ° C and 24 mm Hg than individuals. Rate of water loss was high relative to other desert arthropods but comparatively low for an ant.